Impact of Dairy Co-operative Society on the Knowledge Level of Dairy Farmers in Rajasthan (Indian Journal of Extension Education, 2015)
Present study was conducted on a total 120 dairy farmers having minimum two milch animals which include 60 member and 60 non-member of dairy co-operative, selected from eight villages of Sikar district of Rajasthan during the year 2014, to ascertain the impact of dairy co-operative on dairy farmers in terms of their knowledge level about scientific dairy farming practices. Findings revealed that majority of the respondents (53.33%) of both the categories possessed moderate knowledge about scientific dairy farming practices. It was found that knowledge level of member dairy farmers was significantly higher than the non-member dairy farmers except: knowledge about artificial insemination, deworming and feeding of green fodder.